A novel 1,3,5-Triazine-based fluorescent probe with large Stokes shift for the detection of Hg(II) and its application in cell, zebrafish and tobacco imaging - He, Yuan; Chen, Yun-Feng; Li, Cong-Cong; Wang, Mao-Hua; Li, Lin; Chen, Guo-Yu; Zhang, Li-Meng; Wang, Lin-Qing; Wang, Jian-Yong (Journal of photochemistry and photobiology. A, Chemistry., 2024)
[Display omitted] •A fluorescent probe based on 1,3,5-Triazine was designed and synthesized to detect Hg(Ⅱ).•The novel fluorescent probe exhibited high selectivity, good stability, large Stokes shift (100 nm).•The novel fluorescent probe has been successfully used for cell and zebrafish imaging.•The novel fluorescent probe has successfully detected Hg(II) in tobacco. Non-biodegradable, bioaccumulative, and highly toxic, mercury(II) poses a significant threat to both ecosystems and human health. Extensive data indicates that even extremely low levels of Hg(II) can cause significant harm to human health. In this paper, the thiocarbonate specific recognition site was used for the detection of Hg(II), which was successfully synthesized by the hydroxyl group of 1,3,5-Triazine with phenyl chlorothiocarbonate. The probe exhibited advantages of high sensitivity (0.253 μM), good selectivity, large Stokes shift (100 nm), and good biocompatibility. The probe TzAr-Nap-Hg successfully fluorescently imaged Hg(II) in cells, zebrafish and tobacco, making it possible to detect the content of Hg(II) in agricultural and sideline products.